Herpes zoster, its epidemicity, and association with chicken pox - Krone, F. (The University of Edinburgh, 1924)
Hutchinson many years ago, while raising the question as to whether Herpes Zoster should be classified as a neurosis or an exanthem, is reported to have said, "My own suspicion is that i t belongs to neither of these classes, and further, I feel convinced that whoever may succeed in unravelling the mystery which at present surrounds it , must at the same time make a discovery in Physiology**

The clinical observations that certain cases of Herpes Zoster are infectious and occur in small epidemics; that the disease may be associated with Chicken Pox; and that its etiology and mode of infection are entirely unknown, add further great interest to this particular malady. These facts amongst others led me to decide to investigate this much discussed and in many respects obscure disease.

SCOPE OF THESIS. (1 ) I decided to investigate the records of all the cases of Herpes Zoster, 270 in number, which have been seen in the Dermatological Department of the Royal Infirmary Edinburgh, during the last sixteen years, that is for the years 1907 to 1922 inclusive, with a view to gaining critical information as to Etiology, Predisposing causes, Distributional characteristics, Age and Seasonal incidence, and Epidemicity of Herpes Zoster. (2 ) I have decided to lay special stress on the Epidemicity of Herpes Zoster. (3) I will discuss at some length the division of Herpes Zoster into Idiopathic and Symptomatic, such a differentiation being of the greatest importance in connection with the association of certain cases of Herpes Zoster with Chicken Pox. (4) Much attention has lately been given to the association of Herpes Zoster and Chicken Pox, and realising Herpes Zoster to be infectious and capable not only of infecting another person with Herpes Zoste but also with Chicken Pox, I decided to investigate the recorded cases in the literature of this association of the two diseases, and also to consult the articles dealing with this subject, in order to make a critical digest of the literature, with a view to drawing some conclusions on this matter. Further, to show from clinical manifestations the association of the Idiopathic variety of Herpes Zoster with Chicken Pox. I t would perhaps be as well to make mention of the fact here, that such an investigation would necessarily be curtailed because:- (1) Although the Dermatological Department of the Royal Infirmary probably records more cases of Herpes Zoster than any other institution in Edinburgh, it does not drain a ll the cases of the Town, many going to other Medical wards, Leith and other hospitals, and many being seen by general practitioners only. Further the disease not being notifiable all the cases cannot be recorded, so that an absolute and true record of the Epidemicity of Herpes Zoster as representing the whole town cannot be given. However the Royal Infirmary consistently and regularly draws a certain class and part of the community, so that from the records of this special department we can draw a conclusion which is constant, accurate, and which will also give us a very near idea as regards the characteristics of this disease for the whole community of Edinburgh. (2) Chicken Pox not being notifiable we cannot give statistics showing that an epidemic of Herpes Zoster occurs at the same time as an epidemic of Chicken Pox, but we can however clinically show the close association of the two diseases, as w ill be described later.